Sensors and Instrumentation, Volume 5 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Wee Sit, Evro.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Sensors and Instrumentation, Volume 5. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the fifth volume of ten from the Conference brings together contributions to this important area of research and engineering. Th e collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Experimental Techniques • Smart Sensing • Rotational Eff ects • Dynamic Calibration • Systems & Sensing Technologies • Modal Transducers • Novel Excitation Methods.
1 Phase Control of RF Cavities -- 2 Smart Setup and Accelerometer Mounting Check for Vibration Measurements -- 3 NVH Development at Achates Power -- 4 35 Years with Structural Measurements at Bruel & Kjær -- 5 Measuring Violin Bow Force During Performance -- 6 Synthesizing Uncorrelated Drive Files for MIMO Transmissibility Measurements on Road Simulators -- 7 Calibration Techniques for Non-Contacting Force Excitation Part 1. Frequency Domain Methods -- 8 Calibration Techniques for Non-Contacting Force Excitation Part 2. Time Domain Methods -- 9 Responses of Structures to SDoF vs MDoF Vibration Testing -- 10 High Gap Maglev Model and Experimental Validation -- 11 Blind identification of Operational Deflection Shapes from Continuous Scanning Laser Doppler Vibrometry -- 12 Digital Image Correlation for Timing Belts Dynamic Characterization: Potentials and Critical Aspects -- 13 Stiffness Characterization of an Inflated Airbag Based Three Axis Motion Platform -- 14 Experimental Evaluation of the Force Transmissibility of Phononic-Inspired Vibration Isolators -- 15 Vibro-Impact NES: A Correlation Between Experimental Investigation and Analytical Description -- 16 Fixed-Base Modal Testing Using the NASA GRC Mechanical Vibration Facility -- 17 Observer-based Distributed Controllers Design for A Cantilever Beam -- 18 Experimental Characterization of a Tuned Vibration Absorber.
Keywords: Mechanics, Applied; Solids; Multibody systems; Vibration; Measurement; Measuring instruments; Solid Mechanics; Multibody Systems and Mechanical Vibrations; Measurement Science and Instrumentation